TRAINING OF COMPETENCIES IN ELECTRONIC ENGINEERING THROUGH ARTIFICIAL INTELLIGENCE: EVIDENCE, CHALLENGES AND CONTRIBUTIONS FROM EDUCATIONAL PSYCHOLOGY AND UNIVERSITY TEACHING AT THE POPULAR UNIVERSITY OF CESAR - MONTERO , SANDRA EMILIA MOLINA; DUARTE , DORIXY DE ARMAS; FERNÁNDEZ , CARLOS EDUARDO DÍAZ; FERNÁNDEZ , JOSÉ LUIS ZABALETA; DAZA , SANDRA MILENA DAZA; PABON , CARMEN ELENA AMAYA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This article presents the integration of artificial intelligence in electronic engineering education, identifying emerging evidence, psychological challenges, and teaching considerations relevant to the Universidad Popular del Cesar. It shows a quantitative methodological design that combines surveys of teachers and surveys of electronic engineering students, analysis of ranges of uses of AI tools and a literature review on attitudes and psychological effects. The preliminary results highlight potential improvements in performance, self-efficacy and conceptual understanding, while identifying challenges such as biases, technological dependence and the need for teacher training for responsible and ethical implementation at the Universidad Popular del Cesar. It was achieved with the collection of empirical evidence and interpretation from approaches of educational psychology and teaching practices, to advance in a responsible and ethically grounded implementation at the Popular University of Cesar.